FREQUENCY AND CLINICAL EPIDEMIOLOGICAL DESCRIPTION OF MAIN BRONCHOPULMONARY DISEASES IN THE MILITARY - Mokhida A. Jakbarova; Mokhigul A. Juraeva (Central Asian Journal of Medicine, 2025)
Studying the prevalence of major bronchopulmonary diseases is one of the important indicators determining the health of the population, including among the military. The data obtained as a result of a number of studies have different indicators, which are related to living and working conditions, the methodology of the data obtained, diagnostic methods and the availability of preventive measures. The purpose of our study; to study the frequency of detection and clinical epidemiological characteristics of major bronchopulmonary diseases in the military. In doing so, we set ourselves the task of studying community-acquired pneumonia, chronic nonspecific lung diseases (chronic bronchitis, chronic obstructive pulmonary disease, bronchial asthma) among the military. In order to obtain complete information about the main symptoms and course of the diseases, prospective studies were conducted in patients treated in 2023. For this, 273 servicemen from the Tashkent Central Military Clinical Hospital were recruited and divided into the following age groups: under 29 years old, 30-39 years old, 40-49 years old, and 50 and older. People aged 60 and 70 were not divided into a separate group due to the low number of participants in the study. Of these, 33.7% (92) were relatively healthy servicemen with no pulmonary diseases, 33.7% (92) were diagnosed with community-acquired pneumonia, and 32.6% (89) with chronic nonspecific pulmonary diseases (CNPD).